2023
DOI: 10.1126/sciadv.add6165
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding protein DDX5 restricts RORγt + T reg suppressor function to promote intestine inflammation

Abstract: Retinoid-related orphan receptor (RAR) gamma (RORγt)–expressing regulatory T cells (RORγt + T regs ) play pivotal roles in preventing T cell hyperactivation and maintaining tissue homeostasis, in part by secreting the anti-inflammation cytokine interleukin-10 (IL-10). Here, we report that hypoxia-induced factor 1α (HIF1α) is the master transcription factor for Il10 in RORγt + T regs . This cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…For instance, loss-of-function variants of MDA5, an important member of the RNA helicase family, have been implicated in very early onset IBD 40 . DDX5 has been shown to regulate the function of epithelial tuft cells and intestinal regulatory T cells, which control the microbial repertoire and inhibits intestinal inflammation 41 , 42 . However, the roles of most RNA helicases in regulating intestinal function remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, loss-of-function variants of MDA5, an important member of the RNA helicase family, have been implicated in very early onset IBD 40 . DDX5 has been shown to regulate the function of epithelial tuft cells and intestinal regulatory T cells, which control the microbial repertoire and inhibits intestinal inflammation 41 , 42 . However, the roles of most RNA helicases in regulating intestinal function remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al. reported that DDX5 suppresses HIF‐1‐dependent expression of the anti‐inflammation cytokine interleukin‐10 (IL‐10) in certain regulatory T cells under hypoxic conditions (Ma et al., 2023). On the other hand, in the present study, we found that aberrant expression of DDX5 activates HIF‐1 signaling in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the dual regulatory potential of HIF-1α on T cells, its impact on IL-17-producing Treg differentiation and function has been studied. It has been confirmed that HIF-1α is one of the factors promoting IL-10 production in IL-17-producing Tregs [ 102 ]. High levels of HIF-1α are expressed in IL-17-producing Tregs within the lamina propria of the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Hif1a transcription is repressed, inhibiting HIF-1α-induced IL-10 production in IL-17-producing Tregs (Fig. 1 ) [ 102 ].…”
Section: Introductionmentioning
confidence: 99%